Review: phytochemistry and medicinal properties of Solanum torvum fruits. Issue 1 (1st January 2020) - Darkwah, Williams Kweku; Koomson, Desmond Ato; Miwornunyuie, Nicholas; Nkoom, Matthew; Puplampu, Joshua Buer
Abstract : Background: Most plants have medicinal properties, which they achieve from certain secondary metabolites. Phytochemicals are compounds produced by plants. They may affect health but are not-essential nutrients as our diet does not require them to sustain life in the same way as vitamins and minerals. Objectives: The study reports the phytochemistry and medicinal properties of Solanum torvum fruits. Methods: A search of database sites such as PUBMED, Google Scholar, and Web of Science as well as other sources of literature available across public libraries was conducted to obtain information related to the topic. Results: Here, we review the numerous medicinal properties of S. torvum (cardio and nephro protection, anti-hypertensive, analgesic, anti-inflammatory, anti-ulcer, anti-microbial activities) and relate them to the underlying phytochemicals and their biological actions. Conclusion: This exposure is expected to provide researchers with updated information on S. torvum health benefit properties and related phytochemicals, which merit future research for developing pharmacological drugs aimed at curing ailments or diseases, and for possible use in preventive medicine.